The Effects of the 2010 Affordable Care Act Dependent Care Provision on Family Structure and Public Program Participation among Young Adults - Pinka Chatterji; Xiangshi Liu; Baris K. Yörük (Center for Economic Studies and ifo Institute (CESifo), 2018)
We use difference-in-difference methods and data from the 2008 Survey of Income and Program Participation to test whether the ACA dependent care provision is associated with family structure and public program participation among young adults. Findings indicate that implementation of the provision is associated with 10 and 15 percent reductions in the likelihoods of being married and cohabitating, respectively, and a 6 percent increase in the likelihood of being single. The provision is associated with a 12 percent reduction in being a single parent, as well as reductions in young adults' participation in SNAP, TANF and WIC.
Keywords: I11; 330; affordable care act; ACA; dependent care; health insurance; family structure; public program participation; marriage; fertility; cohabitation